The Prevalence of Headache Among the Main Symptoms in the Diagnosis of Lung Diseases: an Integrative Review - Clarindo, José Fernando Muniz; Lopes, Thiago Luís Marques; Costa, Bruna Tháisla Lima da; Saboya, Melissa Fiuza; Barcelos, Lucas Eduardo Pinho; Vieira, Natanael Miranda; Karam, Rachel Sobreira; Filho, Vilmar Cesar Diogenes de Aquino; Ripardo, Danylo da Silva; Oliveira, Lierlly Leitão de; Siqueira, Gustavo Moreira; Penha, Guilherme Matos da; et al. (Headache Medicine, 2023)
Full abstract in PDF.